(untitled) (Revista Música, 1999)
This study is primarily concerned with the background to "DerKreidekreis", Zemlinsky's setting of a Chinese drama by Alfred Henschke (pen name 'Klabund', 1890-1928). This was the last of Zemlinsky's stage works to be performed during his lifetime. Indeed, it was the last to be performed anywhere (apart from a solitary production at Nuremberg in 1955) until the slow revival of interest in his music. In terms of scholarship, Horst Weber's monograph, published in 1974, was the first landmark in this process, as well as the first-ever biography and academic study of Zemlinsky in any language. Unlike Schreker, who benefitedfrom three biographies by the time he was 43, Zemlinsky was given only a special issue of the Prague music journal Auftakt for his fiftieth birthday in 1921. A year later the Universal Edition house journal Ausbruch published three short tributes to Zemlinsky as composer (by Franz Werfel) as conductor (by Heinrich Jalowetz) and as teacher (by Erich Korngold) - certainly a distinguished trio. But the general accounts of contemporary music of the time, such as those by Rudolf Louis, Oscar Bie, H. J. Moser and Adolf Weissmann either refer fleetingly to Zemlinsky or ignore him altogether.